2017
DOI: 10.1159/000464298
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Approach for Treatment of Seminal Vesicle Cyst Associated with Ipsilateral Renal Agenesis

Abstract: Objectives: We reviewed the clinical presentation and approach for the treatment of symptomatic seminal vesicle cyst associated with ipsilateral renal agenesis while presenting our experience with a series of 5 patients treated with minimally invasive surgery for Zinner syndrome. Materials and Methods: Between the years 2008 and 2016, we operated on 5 patients who presented with symptomatic seminal vesicle cyst and ipsilateral renal agenesis. Patients' charts and medical records were reviewed and compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 18 publications
0
27
0
4
Order By: Relevance
“…Calcification is best observed in noncontrast CT scans. Density: Cyst density is one of the determining factors in the classification of seminal vesicle lesions. In literature, it has been reported that the CT value of a cyst with liquid (water‐like) content is <20 HU (type I) and the CT value of a cyst with protein or haemorrhage content is higher than 30–40 HU (type II; Bosniak, ; Campora et al, ; Fiaschetti et al, ; Kenney & Leeson, ; Kord et al, ; Naval‐Baudin et al, ). Some studies have reported purulent compositions of cysts with CT values higher than 30–40 HU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcification is best observed in noncontrast CT scans. Density: Cyst density is one of the determining factors in the classification of seminal vesicle lesions. In literature, it has been reported that the CT value of a cyst with liquid (water‐like) content is <20 HU (type I) and the CT value of a cyst with protein or haemorrhage content is higher than 30–40 HU (type II; Bosniak, ; Campora et al, ; Fiaschetti et al, ; Kenney & Leeson, ; Kord et al, ; Naval‐Baudin et al, ). Some studies have reported purulent compositions of cysts with CT values higher than 30–40 HU.…”
Section: Discussionmentioning
confidence: 99%
“…Infertility, haematuria, and haematospermia are some of the cases that may also bring a patient to medical attention. Due to its nonspecific signs and symptoms, Zinner syndrome may be missed or misdiagnosed (Campora et al, ; Fiaschetti et al, ; Kord et al, ; Slaoui et al, ). The objectives of the present study are to detail this syndrome's abnormal anatomy, define the role of noninvasive imaging in diagnosis and management, and propose a seminal vesicle cyst classification through imaging to help stratify its management.…”
Section: Introductionmentioning
confidence: 99%
“…Minimally invasive surgery involving laparoscopic or robotic assisted excision of the cyst appears to be the modality of choice for symptomatic patient and is associated with a favorable outcome and results in resolution of symptoms in the majority of the cases. [ 11 ]…”
Section: Discussionmentioning
confidence: 99%
“… 2 Since then, minimally invasive approaches have become favored in treatment of seminal vesicle pathology due to better visualization of pelvic anatomy, shorter hospital stay, and faster patient recuperation. 3 The use of laparoscopy paved the way for robotic-assisted surgery, with comparable patient outcomes and heightened surgeon comfort. 4 Specifically, Passerotti et al showed that robotic resection of seminal vesicle cysts and prostatic utricles in children and adolescents yielded desirable outcomes.…”
Section: Discussionmentioning
confidence: 99%